Potential Enhancements in Titanium Dental Implants Using Graphene Coatings: A Preliminary Scoping Review - Ayoub, Giuma; Lemamsha, Hamdi; Alzarrug, Faisal; Salem, Showg; Agila, Nora (Sharwes Scientific Journal, 2024)
In the evolving field of dental implantology, graphene coatings represent a significant innovation with the potential to improve implant success. This scoping review synthesises research on graphene-coated dental implants' biocompatibility, antibacterial properties, and effectiveness. It aims to offer a comprehensive overview, identify research gaps, and direct future studies, highlighting graphene's potential to revolutionise implant technology and enhance patient outcomes.